2020
DOI: 10.3390/plants10010071
|View full text |Cite
|
Sign up to set email alerts
|

The Exploitation of Local Vitis vinifera L. Biodiversity as a Valuable Tool to Cope with Climate Change Maintaining Berry Quality

Abstract: (1) Background: The associated increase in global mean surface temperature together with raised atmospheric carbon dioxide (CO2) concentration is exerting a profound influence on grapevine development (phenology) and grape quality. The exploitation of the local genetic diversity based on the recovery of ancient varieties has been proposed as an interesting option to cope with climate change and maintaining grape quality. Therefore, this research aimed to characterize the potential fruit quality of genotypes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…The average daily temperature is +8.9 °C, with an absolute high of +39 °C and a low of -34.5 °C, according to average yearly statistics. Singh et al, 2018;Delrot et al, 2020;Volynkin et al, 2020;Antolín et al, 2020). Variety assortment enhancement is a normal task that involves increasing the assortment's quality and upgrading varieties (Cichi et al, 2019;Magomedov et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The average daily temperature is +8.9 °C, with an absolute high of +39 °C and a low of -34.5 °C, according to average yearly statistics. Singh et al, 2018;Delrot et al, 2020;Volynkin et al, 2020;Antolín et al, 2020). Variety assortment enhancement is a normal task that involves increasing the assortment's quality and upgrading varieties (Cichi et al, 2019;Magomedov et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Among these, temperature and atmospheric CO 2 are the most highlighted climate elements for temperate tree crops. Extensive research in tree phenology has demonstrated that the increase in temperature and atmospheric CO 2 levels ultimately influences the number of chill hours required for dormancy breaking and the yield and fruit quality of temperate fruit crops [10,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (examples are given in Tables 1 and 2). Several studies have evaluated the productivity of temperate fruit crops with the current status of global climate change [4,33,[44][45][46][47][48][49][50][51][52][53].…”
Section: Climate Change and Temperate Fruit Productivitymentioning
confidence: 99%
“…AMF are naturally associated with grapevines, providing some benefits to the plant, although the effects are dependent on many factors, including variety [69,70]. It has been observed that the association of V. vinifera L. cv.…”
Section: Impact Of Beneficial Microbes To Enhance the Content Of Specialized Metabolitesmentioning
confidence: 99%